Knight and day - Mangold, James; Pink, Steve; Garner, Todd.; Konrad, Cathy; O'Neill, Patrick; Diaz, Cameron; Cruise, Tom, 1962-; Grace, Maggie, 1983-; Blucas, Marc, 1972-; Dano, Paul, 1984-; Sarsgaard, Peter; Davis, Viola, 1965-; et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2010)
"When a small-town girl named June (Diaz) meets a mysterious stranger, she thinks she's found the man of her dreams. But she soon discovers he's a fugitive super-spy, who thrusts her into a thrilling cat-and-mouse chase that spans the globe. As the bullets and sparks fly, June must decide if her 'Knight' in shining armor is a dangerous traitor or the love of her life"--Container.
Special features: Wilder knights and crazier days; Knight and "Someday", featuring the Black Eyed Peas and Tom Cruise; Viral video: soccer; Viral video: kick.
Director of photography, Phedon Papamichael ; film editors, Michael McCusker, Quincy Z. Gunderson ; music, John Powell.
Tom Cruise, Cameron Diaz, Peter Sarsgaard, Viola Davis, Jordi Molla, Paul Dano, Maggie Grace, Marc Blucas, Celia Weston.
MPAA rating: PG-13; for sequences of action violence throughout, and brief strong language.
DVD, region 1, widescreen (2.40:1) presentation ; Dolby Digital 5.1 surround.
English (5.1 Doby Digital), French (Dolby Surround) or Spanish (Dolby Surround) dialogue; Spanish subtitles; English subtitles for the deaf and hard of hearing; closed -captioned.
Keywords: Spies -- Drama; Man-woman relationships -- Drama; Video recordings for the hearing impaired; Action and adventure films; Comedy films; Feature films; Spy films